Post-traumatic Effects in Survivors of Childhood Sexual Abuse: A Study Literature - Dhyatmika, Mahatma Acintya; Hermahayu; Faizah, Rayinda (Universitas Muhammadiyah Yogyakarta, 2024)
Childhood sexual abuse can result in long-term effects that remain in the survivors to confront and encounter continually. This study aimed to examine behavioral indicators that indicate trauma, which is one of the long-term effects of child sexual violence against children. The study used a literature study technique. There were three behavioral indications developed as long-term consequences of trauma endured by survivors of child sexual abuse. The first indicator was cognitive distortions characterized by self-blame, self-criticism, and a sense of worthlessness. Then, concerns regarding emotional regulation, which present persistent feelings of anxiety or sadness, can appear as the second implication. The last behavioral indication was difficulties regarding the ability to resist impulsive urges, evidently via the engagement in substance misuse and the development of deviant sexual conduct.